The settlement of the Iatrus fort in the 6th century CE. - von Bülow, Gerda (Balcanica Posnaniensia. Acta et studia, 1990)
The article concerns settlement in the fortress of Iatrus in the 6th century AD. The research problem includes the reconstruction of the functioning of the settlement in Late Antiquity and determining the moment of its decline. The aim of the work is to analyze archaeological material and confront it with written sources. The author applies archaeological and historical methods. The most important results indicate that Iatrus functioned as a settlement and military point also in the 6th century, as confirmed by both archaeological finds and written sources (e.g., Procopius). The settlement was resettled after destruction in the 5th century, and its functioning ended only around 600 AD in connection with Avar and Slavic invasions. The conclusion confirms the continuity of settlement and the importance of Iatrus in the defensive system of the late Empire.